Soliton trains in dispersive media: Свойства нелинейных биофизических систем со сложной внутренней структурой - Engelbrecht, Jüri; Peets, Tanel; Tamm, Kert (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
In this paper two Boussinesq-type mathematical models are described which lead to solitonic solutions. One case corresponds to microstructured solids, another case to biomembranes. The emergence of soliton trains in both cases is demonstrated by using numerical simulation. The pseudospectral method guarantees the high accuracy in computing. The significance of the nonlinearities — either deformation-type or displacement-type, is demonstrated.